2019
DOI: 10.1007/s40617-019-00395-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Self-Evaluation to Enhance Performance in Competitive Dancers

Abstract: First, I would like to acknowledge my thesis advisor, Dr. Raymond Miltenberger. I appreciate you always pushing me in order to help me be as successful as possible during this program. Your time, dedication, and feedback has been a significant factor in my success. I would also like to thank my thesis committee members, Dr. Kimberly Crosland and Dr. Kwang-Sun Cho Blair for assisting me in developing quality work. Finally, I would like to acknowledge Cassandra Bochnak for all the time and effort she has put int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Finally, future researchers could evaluate this same intervention implemented by the trainees themselves, using a video of their performance and the TA to analyze their own performance of the skill. Similar research has shown video self-evaluation to be effective with yoga and dance (Downs et al, 2015;Giambrone & Miltenberger, 2020). Further evaluations of video self-evaluation would be valuable because it represents a more efficient form of video feedback that would be more accessible to a variety of athletes.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, future researchers could evaluate this same intervention implemented by the trainees themselves, using a video of their performance and the TA to analyze their own performance of the skill. Similar research has shown video self-evaluation to be effective with yoga and dance (Downs et al, 2015;Giambrone & Miltenberger, 2020). Further evaluations of video self-evaluation would be valuable because it represents a more efficient form of video feedback that would be more accessible to a variety of athletes.…”
Section: Discussionmentioning
confidence: 89%
“…Feedback interventions used in both direct and indirect competition sports experiments included verbal feedback, video feedback, graphic feedback, and public posting. Self-monitoring was utilized only in indirect competition sports experiments, in seven experiments and across several sports, including dance (Giambrone & Miltenberger, 2019), golf (Kirschenbaum et al, 1998), gymnastics (Wolko et al, 1993), figure skating (Hume et al, 1985), speed skating (Wanlin et al, 1997), and swimming (Critchfield & Vargas, 1991; Schonwetter et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Applied behavior analytic teaching procedures have been shown to have a positive impact on dancers’ performance and satisfaction. Some examples of successful applied behavior analytic teaching strategies in the dance context include: descriptive vocal instruction, modeling, and feedback in a behavioral coaching package to teach foundational dance skills (Fitterling and Ayllon 1983 ), publicly posted graphical feedback to improve the performance of competitive jazz dancers (Quinn et al 2017a ), TAGteach to emphasize correct form and technique of dance skills (e.g., Arnall et al 2019 ; Arnall et al 2022 ; Carrion et al 2019 ; Quinn et al 2015 ; Quinn et al 2017b ), precision teaching to build skill fluency in tap dancing (Lokke and Lokke 2008 ; Pallares et al 2021 ), and video-based instructional strategies to increase the accuracy of dance skills (Deshmukh et al 2022 ; Giambrone and Miltenberger 2020 ; Quinn et al 2019 ). Results of these behavioral coaching strategies has shown that the performance of dance skills improved and adverse effects (e.g., avoidance behaviors, fear responses) often associated with coercive training methods were not observed.…”
mentioning
confidence: 99%
“…Results of these behavioral coaching strategies has shown that the performance of dance skills improved and adverse effects (e.g., avoidance behaviors, fear responses) often associated with coercive training methods were not observed. In addition, dancers consistently reported that they enjoyed these teaching strategies and that they were more confident with their dance performance after receiving instruction using these teaching strategies (e.g., Deshmukh et al 2022 ; Giambrone and Miltenberger 2020 ; Quinn et al 2015 ). However, despite the emerging utility and acceptability of behavioral coaching strategies, few dance instructors are aware of the applicability of behavior analysis in dance education.…”
mentioning
confidence: 99%
See 1 more Smart Citation